Adaptive Strategies in Life-History of Bushcrickets (Orthoptera) and Cicadas (Homoptera) to Parasitoids Pressure on Their Acoustic Communication Systems—A Case for Sociality? - Lehmann, Gerlind U. C.; Lakes-Harlan, Reinhard (Frontiers in Ecology and Evolution, 2019)
In sexual reproduction the search for mating partners elevates the individual risks of predation and parasitism. One way to increase mate search effectiveness and reduce search costs is acoustic signaling. However, acoustic orienting parasitoid flies exploit singing hosts, leading to high parasitism rates. Aggregations of males and females at mating and singing in choruses might reduce individual risks by dilution and predator saturation. This mini-review reflects on consequences for host’s acoustic signaling in choruses using the examples of cicadas and bushcrickets. It comes up with the conclusion that despite antagonistic selection pressure by parasitoids, singing in choruses might select for increased, not reduced signaling in males. The time joining and leaving a choir might be crucial: once mated, a refractory period will drop males off the signaling pool, preventing parasitism. In a chorus, fast and loud singing might be highly advantageous, supporting the fittest males. Natural selection might have shaped signaling strategies in choruses, which can probably only be understood when applying individual based dynamic modeling.